Development of a Deep Learning-Based Short Story Listening Learning Model for Fifth-Grade Students at SD Negeri 2 Kulo - Mariani Binti Aripin; Muhammad Hanafi; Aswadi; Jamaluddin Ahmad; Nuraini Kasman; Yusmah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aims to develop a deep learning-based instructional model for teaching short story listening skills to be utilized by teachers in classroom learning. The type of research employed is Research and Development (R&D) using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The product developed is a Deep Learning Lesson Plan (Rencana Pembelajaran Mendalam/RPM) for a short story listening instructional model, which was systematically designed and validated by experts. The validation results indicate a high level of feasibility: content experts scored 96%, language experts 81%, and instructional experts 88%, all categorized as “highly feasible.” A limited trial involving 10 students resulted in an average gain score of 0.40, which, according to Hake, falls into the moderate effectiveness category. A wider trial involving 25 students showed that 6 students were in the low category (g ≤ 0.30), 19 in the moderate category (0.39 < g ≤ 0.70), and none in the high category (g > 0.70). This indicates that the majority of participants experienced significant improvement after the implementation of the instructional model. The results of teacher and student response questionnaires also indicate a high level of effectiveness, with both obtaining an average score of 4.65, categorized as “very good.” In conclusion, the developed deep learning-based instructional model for teaching short story listening skills is effective, valid, and engaging in improving students’ listening skills in an active, critical, and reflective manner, and contributes to the development of innovative and contextual Indonesian language learning in elementary schools.